(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The Book Uchalyas of Laxman Gaikwad and the Cast Stratification shown in the Book are discussed in this article. Massive abuses of civil, political, economic, social, and cultural rights occur as a result of caste prejudice. It is frequently illegal in nations where it occurs, but due to a lack of enforcement and caste bias in the criminal system, victims are largely unprotected. The book is the voice of those who have been marginalized and oppressed by mainstream Indian society, and who have been compelled to remain silent for a long time. As a result, the article aims to investigate the nature of the Uchalya community’s painful identity of being continually labeled as criminal, as well as the obstacles faced by the community as a whole in their daily lives. The British government has branded this group as criminal tribes. Finally, the book calls for the abolition of imposed social and legal limits, as well as social justice, rights, and many forms of reformation and transformation of the Uchalya community.